Working Channel Endoscopic Interlaminar Microdiscectomy: 2-Dimensional Operative Video. Issue 4 (16th July 2018) - Kolcun, John Paul G; Wang, Michael Y
Abstract: This video demonstrates a working channel interlaminar microdiscectomy performed in a patient with significant back and leg pain due to a persistent disc herniation. We describe this technique in detail, describing the endoscopic anatomy and illustrating key steps to safely perform this operation. Due to the limited soft tissue destruction required to access the disc space with this approach, the patient was able to leave the hospital on the day of surgery, and required no pain medication by short-term follow-up a few weeks postoperatively. All procedures performed in studies involving human participants were in accordance with the ethical standards of the institutional and/or national research committee and with the 1964 Helsinki declaration and its later amendments or comparable ethical standards. The patient gave direct consent for the use of the endoscopic footage and associated information from this surgery for the making of this video.